2012
DOI: 10.1123/jsep.34.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Relational Efficacy Beliefs in Physical Activity Classes: A Test of the Tripartite Model

Abstract: This study explored the predictive relationships between students’ (N = 516, Mage = 18.48, SD = 3.52) tripartite efficacy beliefs and key outcomes in undergraduate physical activity classes. Students reported their relational efficacy perceptions (i.e., other-efficacy and relation-inferred self-efficacy, or RISE) with respect to their instructor before a class, and instruments measuring self-efficacy, enjoyment, and effort were administered separately following the class. The following week, an independent obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
3
22
0
7
Order By: Relevance
“…That is, previous research by Jackson and Beauchamp (2010), Jackson, Myers, et al (2012), and Jackson, Whipp, et al (2012) has consistently shown strong positive correlations between RISE and self-efficacy in samples of adolescent tennis players (r = .65, p < .001), high school PE students (r = .69, p < .001; .72, p < .001) as well as college students participating in a tennis class (r = .73, p < .001). Similarly, in the present study we found that RISE and self-efficacy were strongly correlated with an average effect for the overall sample of r = .78 p < .01.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…That is, previous research by Jackson and Beauchamp (2010), Jackson, Myers, et al (2012), and Jackson, Whipp, et al (2012) has consistently shown strong positive correlations between RISE and self-efficacy in samples of adolescent tennis players (r = .65, p < .001), high school PE students (r = .69, p < .001; .72, p < .001) as well as college students participating in a tennis class (r = .73, p < .001). Similarly, in the present study we found that RISE and self-efficacy were strongly correlated with an average effect for the overall sample of r = .78 p < .01.…”
Section: Discussionmentioning
confidence: 71%
“…Based on research by Jackson et al (2008;2009) and Saville et al (2014) it was predicted that frequency of RISErelevant interactions received from coaches would be positively associated with RISE. Also, drawing from research by Jackson and colleagues it was predicted that RISE would be positively correlated with self-efficacy (Jackson, Whipp et al, 2012;Jackson, Myers et al, 2012). The overarching hypothesis, based on Lent and Lopez's (2002) tripartite efficacy perspective and prior research by Jussim et al (1992), was that RISE-relevant coaching behavior would predict ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 8 RISE, which would in turn predict self-efficacy.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Using a 5-point response scale consistent with previous studies, students were instructed to 7 rate their confidence in their own ability on a number of key class requirements, including, 8 "perform well in your swimming/tennis assessments," "be able to teach the skills you cover 9 effectively to others," and, "learn all the skills and strokes you are taught, even the most difficult 10 ones." We excluded two of the original items used by Jackson et al (2012) in light of the factor 11 loadings that these items (i.e., "be physically fit enough to perform well in this class," "follow 12 instructions effectively at all times") displayed in their investigation; that is, these items displayed 13 only 'fair' fit according to Comrey and Lee's (1992) recommendations. In line with the procedures 14 outlined previously for the assessment of RISE beliefs, these seven items were used to measure 15 undergraduates' estimations of their instructor's confidence in their ability ("at this moment in time, 16 how confident do you think your swimming/tennis instructor is in your ability to..."), and to assess 17 the extent to which they felt that their classmates' as a whole were confident in their ability ("at this 18 moment in time, how confident do you think your classmates as a whole are in your ability to…"), 19 and the standard instructions regarding conceptual separation between self-efficacy and RISE (and 20 between each distinct form of RISE) were included.…”
Section: Methodsmentioning
confidence: 99%
“…One week later at time 2, we assessed task self-efficacy, class enjoyment, and 16 self-presentational efficacy beliefs, and the following week, at time 3, participants took part in their 17 end-of-semester assessment. Specifically, students in both activities completed a 20-minute 18 practical exam, during which they undertook a series of technical and instructional tasks specific to 19 their focal activity (see Jackson et al, 2012). Within their assessment, students were required to 20 execute a series of technical skills (i.e., tennis or swimming strokes), and to provide instruction and 21 diagnostic feedback to another student on that person's technical tennis/swimming skill execution.…”
Section: Methodsmentioning
confidence: 99%